2016
DOI: 10.1371/journal.pone.0159145
|View full text |Cite
|
Sign up to set email alerts
|

Chaparral Shrub Hydraulic Traits, Size, and Life History Types Relate to Species Mortality during California’s Historic Drought of 2014

Abstract: Chaparral is the most abundant vegetation type in California and current climate change models predict more frequent and severe droughts that could impact plant community structure. Understanding the factors related to species-specific drought mortality is essential to predict such changes. We predicted that life history type, hydraulic traits, and plant size would be related to the ability of species to survive drought. We evaluated the impact of these factors in a mature chaparral stand during the drought of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
108
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(115 citation statements)
references
References 72 publications
6
108
0
1
Order By: Relevance
“…Theoretically, they can continue to photosynthesize and gain carbon for longer time periods or during less favourable conditions than less drought resistant species, though this is debated (Martínez‐Vilalta & Garcia‐Forner, ). However, a recent study also conducted in the California chaparral during the exceptional 2014 drought found that chaparral species with high cavitation resistance experienced high mortality rates, whereas deeply rooted species had high survival rates (Venturas et al, ). Obviously, although coordination between the P 50 and P close may vary depending on the vegetation‐type, disentangling rooting depth and stomatal behaviour is of value (Feng, Dawson, Ackerly, Santiago, & Thompson, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, they can continue to photosynthesize and gain carbon for longer time periods or during less favourable conditions than less drought resistant species, though this is debated (Martínez‐Vilalta & Garcia‐Forner, ). However, a recent study also conducted in the California chaparral during the exceptional 2014 drought found that chaparral species with high cavitation resistance experienced high mortality rates, whereas deeply rooted species had high survival rates (Venturas et al, ). Obviously, although coordination between the P 50 and P close may vary depending on the vegetation‐type, disentangling rooting depth and stomatal behaviour is of value (Feng, Dawson, Ackerly, Santiago, & Thompson, ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the 2012–2014 drought in California was the most intense drought in the past 1,200 years (Griffin & Anchukaitis, ). A recent study conducted in a southern California native shrubland found that shallow‐rooted species with cavitation resistant xylem experienced the highest mortality levels due to drought, whereas deeply rooted species with xylem vulnerable to cavitation had lower mortality levels (Venturas et al, ). This differential mortality among co‐occurring species due to varying drought survival strategies (Pivovaroff, Pasquini, et al, ) may result in changes in community composition and ultimately biodiversity loss.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, leaves of three of our study species ( C. spinosus , Q. agrifolia , and Q. berberidifolia ) recovered from extreme water deficits (<10% RWC) to 48–66% of their initial pre‐dehydration SWC. These species are evergreens native to chaparral, adapted to maintaining leaves through severe drought events (Venturas et al, ). In this way, they show a degree of “resurrection” type behaviour, such as that found in species that can recover from virtually complete dehydration (>300 pteridophytes and angiosperms [Rascio & Rocca, ];e.g., Boea hygrometrica [Xiao et al, ], Craterostigma wilmsii [Cooper & Farrant, ], Haberlea rhodopensis [Moyankova et al, ], and Selaginella lepidophylla [Eickmeier, ]).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the most recent drought (2012–present) triggered significant dieback and mortality of adult shrubs in many regions throughout southern California, including areas in the center of chaparral distribution. At one chaparral site, stand density was reduced by > 60%, primarily due to mortality that occurred during winter 2014, and some species exhibited > 90% mortality (Venturas et al ., ). The same patterns were also apparent at broader scales (Coates et al ., ).…”
Section: Chaparral Mortality During Extreme Drought Eventsmentioning
confidence: 97%
“…Peak mortality events were associated with very low PDSI values, with high chaparral mortality during winter 2014 during an especially intense period (Fig. ; Venturas et al ., ). If drought duration was the key driver of chaparral mortality, one would predict mortality events to occur repeatedly as the drought continued, rather than the observed episodes of mortality during the periods of highest drought intensity.…”
Section: Chaparral Mortality During Extreme Drought Eventsmentioning
confidence: 97%